Improvement of surfboards’ design and production process - Wozniak, Maciej Kazimierz (2021)
The subject of this thesis is analyzing different ways of producing surf boards, visiting several shaping companies to understand what problems they may have and try to find out possible solutions for them. After that, different types of surfboards and materials used to make them will be described. Next, two surfboards will be made, according to the preferences of majority of the surfers. The first one will be the prototype and the second one, the improved version, also in the ecological aspect. In this work I will focus mainly on the smaller local workshops which made custom boards.